Pengembangan Rancangan Aplikasi Mobile Bisnis Crowdsourcing (Studi Kasus : "PT. Sinergi Ketahanan Pangan") - Muhammad Vionda Novrian; Diah Priharsari; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT. Sinergi Ketahanan Pangan is a company engaged in the chicken farming industry that runs an investment system in the form of crowdfunding with one of its products named Chick-In. Currently, PT. Sinergi Ketahanan Pangan uses website as a media to make crowdfunding investments. This research aims to design a mobile-based crowdfunding application. The method used for designing the application is Prototyping Method. In the early stages, researchers collect data so that what is obtained later is in the form of user characteristics, user objectives, and task scenarios through the interview process that will be summarized into user stories. Furthermore, the data collection results are analyzed and get some results related to user story, target market, user persona, functional and non-functional applications. In the next stage, some of the results of the analysis are used as a basis for designing applications. Application design generates use case diagrams, class diagrams, sequence diagrams, and business processes. Furthermore, some of the design results were used for prototyping, by making low-fidelity prototypes and high-fidelity prototypes using Figma. The results of the prototype were evaluated using the task scenario method and System Usability Scale (SUS) using 5 respondents. Questionnaires are distributed using Google Form media. Task Scenario test results found 6 problems found in respondent 1, respondent 3, and respondent 4. In SUS test results, R1 has the number of scores obtained is 90, R2 has the number of scores obtained is 75, R3 has the number of scores obtained is 78, R4 has the number of scores obtained is 83, and R5 has the number of scores obtained is 75. Then the total average score obtained is 80. This number indicates that the application is categorized as acceptable, grade scale B, and rating excellent. This means that the app can be said to be good or can be used by end-users.